Dante between Furor and Studies - França de Brito, Emanuel (2024)
This article analyzes a polemic of Italian Humanism around Dante Alighieri (1265-1321). In that period, intellectuals such as Cristoforo Landino (1424-1498) and Marsilio Ficino (1433-1499) interpreted Dante’s writing through the platonic prism of the Phaedrus, that is, as someone who was granted the grace to contemplate the divine and the power to describe it. Decades earlier, however, Coluccio Salutati (1331-1406) and Leonardo Bruni (1370-1444) had already attributed to Dante the merit of focusing on formal studies and, with that, being able to develop expressive artifices to his poetry on its own. For the analysis of the different readings, excerpts in which Dante gives evidence of his path and intellectual maturity will be observed, as well as those in which it is possible to observe the poet’s role in the dissemination of formal knowledge in line with his ethical values.